Mental illness stigma after a decade of Time to Change England: inequalities as targets for further improvement. (13th December 2019) - Henderson, Claire; Potts, Laura; Robinson, Emily J
Abstract: Background: England's Time to Change programme to reduce mental health-related stigma and discrimination included a social marketing campaign using traditional and social media, and targeted middle-income groups aged 25–45 between 2009 and 2016. From 2017, the same age group on low to middle incomes were targeted, and the content focused on men's mental health, by changing the advertising and adapting the 'key messages'. This study investigates changes in stigma-related public knowledge, attitudes and desire for social distance in England since Time to Change began in 2008–19 and for 2017–19. Methods: Using data from a face-to-face survey of a nationally representative quota sample of adults for England, we evaluated longitudinal trends in outcomes with regression analyses and made assumptions based on a simple random sample. The pre-existing survey used a measure of attitudes; measures of knowledge and desire for social distance were added in 2009. Results: Reported in standard deviation units (95% CI), the improvement for knowledge for 2009–19 was 0.25 (0.19, 0.32); for attitudes, 2008–19, 0.32 (0.26, 0.39) and for desire for social distance, 2009–19 0.29 (0.23, 0.36). Significant interactions between year and both region and age suggest greater improvements in London, where stigma is higher, and narrowing of age differences. There were significant improvements between 2017 and 2019 in knowledge [0.09 (0.02, 0.16)] and attitudes [0.08 (0.02, 0.14)] but not social distance. Conclusion: The positive changes support the effectiveness of Time to Change but cannot be definitively attributed to it. Inequalities in stigma by demographic characteristics present targets for research and intervention.